Mechanism of action of a bioassay-guided aqueous fraction of Pterocarpus marsupium Roxb hardwood on glucose-dependent insulin secretion - Suresh Kumar Mohankumar; James R. McFarlane (International Journal of Phytomedicine, 2016)
We previously demonstrated that a high molecular weight aqueous fraction of Pterocarpus marsupium Roxb. (PM) hardwood has insulinotrophic properties. However, the pharmacological mechanisms by which this fraction modulates insulin secretion remained unknown. The present study therefore isolated the insulinotrophic activity enriched fraction (AEF) from aqueous extract of PM and examined its pharmacological mechanisms. A bioassay method utilizing insulin secretion from mouse pancreas in vitro, was used to fractionate the insulinotrophic activity of PM and to delineate its pharmacological mechanisms. In addition, the effect of AEF on glucose clearance in normoglycemic, non-diabetic sheep in vivo was examined. The AEF mimicked the effect of sulphonylureas on insulin secretory pathways and modulated insulin biosynthesis. However, unlike tolbutamide, AEF-induced insulin secretion is glucose-dependent. Furthermore, three daily intravenous administrations of AEF had prolonged effects on glucose responsiveness in non-diabetic normal sheep. The use of AEF to combat the adverse effects of hyperglycemia appears to be beneficial by enhancing and sustaining the glucose-dependent insulin secretion processes in pancreas. Of note, the insulinotrophic effect of AEF is prolonged by many hours to days, unlike the numerous conventional insulin secretagogus which over stimulate the β-cells or pose a risk of hypoglycemia.